Mind–Body Exercises for PTSD Symptoms, Depression, and Anxiety in Patients With PTSD: A Systematic Review and Meta-Analysis - Zhu, Lin; Li, Long; Li, Xiao-zhi; Wang, Lin (Frontiers in Psychology, 2022)
Objectives This study aims to systematically analyze the effects of mind–body exercises on post-traumatic stress disorder (PTSD) symptoms, depression, and anxiety in patients with PTSD. Furthermore, it intends to provide scientific evidence-based exercise prescriptions. Methods Chinese (i.e., China National Knowledge Infrastructure, VIP Database for Chinese Technical Periodicals, and Wanfang) and English (i.e., Web of Science, PubMed, the Cochrane Library, and EMBASE) databases were used as data sources to search for studies on the effects of mind–body exercises on symptoms associated with patients with PTSD from January 1980 to November 2020. After a rigorous screening, 16 eligible randomized controlled trials (RCTs) were included in the meta-analysis. Results Mind–body exercises exerted a significant effect on PTSD symptoms [standard mean difference (SMD) = −0.41, 95% confidence interval (CI) −0.64 to −0.19, p < 0.001], depression (SMD = −0.35, 95% CI: −0.55 to −0.15, p < 0.001), and anxiety (SMD = −0.31, 95% CI: −0.74 to −0.12, p < 0.001) among patients with PTSD. Subgroup analysis demonstrated that 60–150 min per session for 8–16 weeks of mindfulness was more effective in improving symptoms in patients with PTSD under 45 years of age compared with other subgroups. For depression, 150–180 min of yoga exercises once per week was effective. For anxiety, the frequency, timing, duration, and type of mind–body exercises that are most effective in relieving anxiety in patients with PTSD cannot be determined at this time due to the limited number of eligible RCTs. Conclusions Mind–body exercises were found to be significantly effective in improving PTSD symptoms, depression, and anxiety in patients with PTSD. Therefore, they can be used as an adjunct to intervention for symptoms of patients with PTSD. However, this conclusion requires further confirmation through additional scientific and objective RCTs. Systematic Review Registration: Unique Identifier: INPLASY2020120072.